2023
DOI: 10.1037/apl0001048
|View full text |Cite
|
Sign up to set email alerts
|

Retreating or repairing? Examining the alternate linkages between daily partner-instigated incivility at home and helping at work.

Abstract: Although research has recognized the straining effects of incivility at work, it is less clear how incivility experiences at home affect employees' daily states and behaviors at work. We argue that partner-instigated incivility-ambiguous aggressions from an employee's partner prior to work may affect helping behavior at work in multiple ways. Building on prior research, which has identified different mechanisms (i.e., resource drain, reactive compensation) linking family and work domains, we argue that whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 139 publications
1
9
0
Order By: Relevance
“…In their study, researchers found that those individuals with higher levels of perspective-taking (+1 SD) were less affected by customer incivility as measured by performance on the Raven test (i.e., fluid memory component of working memory) compared to individuals lower in perspective-taking. Ganster et al (2022) and Cooper et al (2022) found similar effects regarding the moderating effects of perspective-taking on the relationship between incivility and negative emotions. However, Cooper et al (2022) also employed a perspective-taking intervention (study 2) that included writing a narrative essay about the life of an imaginary person in which they were instructed to "Imagine a day in the life of this individual as if you were that person….what this person might be thinking, feeling and experiencing during the day" (pg.…”
Section: Episodic Incivility Intervention Researchmentioning
confidence: 67%
See 4 more Smart Citations
“…In their study, researchers found that those individuals with higher levels of perspective-taking (+1 SD) were less affected by customer incivility as measured by performance on the Raven test (i.e., fluid memory component of working memory) compared to individuals lower in perspective-taking. Ganster et al (2022) and Cooper et al (2022) found similar effects regarding the moderating effects of perspective-taking on the relationship between incivility and negative emotions. However, Cooper et al (2022) also employed a perspective-taking intervention (study 2) that included writing a narrative essay about the life of an imaginary person in which they were instructed to "Imagine a day in the life of this individual as if you were that person….what this person might be thinking, feeling and experiencing during the day" (pg.…”
Section: Episodic Incivility Intervention Researchmentioning
confidence: 67%
“…Because the focus of episodic incivility is on transient, shortterm reactions to incivility, these responses could easily appear as additional mediators of research designs of longer duration. For example, work by Ganster et al (2022) showed that partner-instigated incivility was associated with cognitive depletion and negative mood and these outcomes served as mediators (emotional and cognitive) of helping behaviors at work. It is unknown, however, to what extent those workplace helping behaviors may have created a more supportive environment among study participants' coworkers thereby decreasing the likelihood of workplace incivility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations